2019
DOI: 10.1021/acs.jafc.9b02879
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Nitrogen-Containing Flavonoid in the Fruits of Cumin (Cuminum cyminum L.) with Anti-inflammatory Activity

Abstract: The dried seeds of Cuminum cyminum L. have been traditionally used as food and medicine. To explore its chemical composition and anti-inflammatory activity, four new compounds (1−4) along with five known compounds (5−9) were isolated from the seeds in the present study. The chemical structures of the new compounds were identified as follows: 3), and (3,4,5-trihydroxy-6-((5-hydroxy-2-(4-hydroxyphenyl)-4-oxo-4H-chromen-7-yl)oxy)tetrahydro-2H-pyran-2-yl)methyl 3-(4-isopropylphenyl)-2-methoxypropanoate (4). Compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Considerable expression of three major mitogens activated protein kinases (MAPKs) namely C‐Jun N‐terminal kinases (JNK), extracellular signal‐regulated kinases (ERKs), and p38 acts as the major signalings involved by cumin polysaccharides to impart their immunostimulant effect and to battle against inflammation, infections, and abnormal cells whereas NF‐κB act as a downstream component of MAPKs signaling pathways. In another study, Kang et al (2019) described the inflammation‐protecting mechanism of flavonoids isolated from cumin seeds and observed that these compounds effectively downregulated the nitric oxide synthase and cyclooxygenase‐2 (COX‐2) enzymes. The enzyme COX‐2 is crucial for prostaglandin release, which exert important function in various inflammation associated disorders, such as paw edema, rheumatoid arthritis, bronchitis, and so forth.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Considerable expression of three major mitogens activated protein kinases (MAPKs) namely C‐Jun N‐terminal kinases (JNK), extracellular signal‐regulated kinases (ERKs), and p38 acts as the major signalings involved by cumin polysaccharides to impart their immunostimulant effect and to battle against inflammation, infections, and abnormal cells whereas NF‐κB act as a downstream component of MAPKs signaling pathways. In another study, Kang et al (2019) described the inflammation‐protecting mechanism of flavonoids isolated from cumin seeds and observed that these compounds effectively downregulated the nitric oxide synthase and cyclooxygenase‐2 (COX‐2) enzymes. The enzyme COX‐2 is crucial for prostaglandin release, which exert important function in various inflammation associated disorders, such as paw edema, rheumatoid arthritis, bronchitis, and so forth.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Cumin oil exhibits significant antimicrobial properties (Belal et al, 2017). Kakarla et al (2017) Seeds and fruits (Kang et al, 2019;Goodarzi et al, 2020) Luteolin-7-O-glucoside (Pubchem CID: 4444241) (Goodarzi et al, 2020) Apigenin (Pubchem CID: 4444100) (Kang et al, 2019;Goodarzi et al, 2020) Apigenin-7-O-glucoside (Pubchem CID: 4444290) (Goodarzi et al, 2020) 6. Allylbenzene Eugenol (Pubchem CID: 13876103)…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 3 more Smart Citations